Hungarian Monitoring, 28 February 1989 . [Magyar rádiófigyelő], 1989. február 28 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Bush and the Tower case - Situation in Kosovo - Remembering the Sumgait carnage - China ready to open trade office in South Korea - Time to revise revisionism in the USSR Domestic Affairs: - Hungarian Socialist Workers' Party (MSZMP) Central Committee in session - Very strong reaction in Bucharest to Gyula Horn's speech in Geneva - European Parliament delegation in Hungary joined today by vice-President Otto Habsburg - Hungarian Socialist Workers' Party (MSZMP) and National Council of Trade Unions (SZOT) representatives think it possible that roundtable political talks might take place in Hungary - Rehabilitation of the "Tiszatáj" periodical editors - Independent organizations and groups do not wish to give up their plans to march to Freedom Square on March 15 and symbolically occupy Hungarian TV HQ Economy: - Last year for light industry in the balance - Government works out new tax policy Külpolitika: - Bush és a Tower-ügy - Koszovói helyzetkép - A szungajti vérengzésekről megemlékezés - Kína kész kereskedelmi iroda nyitására D-Koreában - A SZU-ban eljött a revizionizmus revíziójának ideje Belpolitika: - MSZMP KB ülés - Sztrájktörvény tervezete az ipari bizottságban és a SZOT-ban - Bukarestben nagyon kemény reakciót váltott ki Horn Gyula Genfben elhangzott beszéde - A Magyarországon tartózkodó Európa Parlament delegációjához ma csatlakozott Habsburg Ottó alelnök - Az MSZMP és a SZOT képviselői lehetségesnek tartják, hogy Magyarországon is létrejöjjön politikai kerekasztal megbeszélés - A Tiszatáj folyóirat szerkesztőinek rehabilitálása - A független szerveztek és csoportok nem kívánnak lemondani tervükről, hogy március 15-én a Szabadság térre vonuljanak és jelképesen lefoglalják a MTV-t Gazdaság: - A könnyűipar tavalyi mérlege - Új adópolitikát dolgoz ki a kormány